Epidemiological case-control study on contact sensitisation in female foot care specialists with occupational contact dermatitis: Patch test data of the Information Network of Departments of Dermatology (IVDK), 2008 to 2022 - Brans, Richard; Schröder-Kraft, Claudia; Gina, Michal; Heratizadeh, Annice; Weisshaar, Elke; Bauer, Andrea; Strom, Kerstin; Skudlik, Christoph; Schubert, Steffen (Contact dermatitis, 2024)
Background Mainly women work as foot care specialists (FCS). They are at risk to develop occupational dermatitis (OD). Objectives The objective of this study is to describe the contact sensitisation pattern of female FCS with OD. Methods In a retrospective study, patch test and clinical data collected by the Network of Departments of Dermatology (IVDK) from 2008 to 2022 were analysed. Data of 116 female FCS with OD were compared with data of 13 930 female patients with OD working in other professions and 78 612 female patients without OD. Results Hand dermatitis (93.1%) was significantly more common and face dermatitis (0.9%) significantly less common in female FCS with OD compared to other female patients with or without OD. Frequent suspected allergen sources were disinfectants, gloves, leave-on and nail cosmetics. Occlusion and wetness were important co-factors. The most common diagnoses were irritant contact dermatitis (26.7%) and allergic contact dermatitis (21.6%). No sensitisation to any of the baseline series allergens was significantly more frequent in female FCS with OD than in the two control groups. However, sensitisations to allergens which FCS are abundantly exposed to, including fragrances, preservatives, rubber ingredients and disinfectants, were most common. Conclusions FCS should be aware of the OD risk and prevention should be promoted.